2006
DOI: 10.1534/genetics.106.055632
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Length Differences Between Humans and Chimpanzees at Autosomal Loci Are Not Found at Equivalent Haploid Y Chromosomal Loci

Abstract: When homologous microsatellites are compared between species, significant differences in mean length are often noted. A dominant cause of these length differences is ascertainment bias due to selection for maximum repeat number and repeat purity when the markers are being developed. However, even after ascertainment bias has been allowed for through reciprocal comparisons, significant length differences remain, suggesting that the average microsatellite mutation rate differs between species. Two classes of mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Our analysis was focused on the differences in short tandem repeats of mono-, di-and trinucleotide units. Several authors claim that the human repeats are on average longer than the chimpanzee ones (Kayser et al 2006;Vowles and Amos 2006;Webster et al 2002). Our results confirm this observation, but we concluded that the asymmetry is too weak to warrant the construction of two independent mutational probabilities and since the ancestral state of the repeats is not known we can only compile the mutational probabilities based on the relative differences.…”
Section: Replication Slippage Versus Point Mutationssupporting
confidence: 77%
“…Our analysis was focused on the differences in short tandem repeats of mono-, di-and trinucleotide units. Several authors claim that the human repeats are on average longer than the chimpanzee ones (Kayser et al 2006;Vowles and Amos 2006;Webster et al 2002). Our results confirm this observation, but we concluded that the asymmetry is too weak to warrant the construction of two independent mutational probabilities and since the ancestral state of the repeats is not known we can only compile the mutational probabilities based on the relative differences.…”
Section: Replication Slippage Versus Point Mutationssupporting
confidence: 77%
“…1998). The degree of polymorphism seems to be positively correlated with microsatellite length (Kayser et al . 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, using current algorithms, microsatellite sequences do not align well and, at first sight, might resemble sequences with no common ancestry; the above statistical approach, which assumes a “perfect” alignment (Margulies and Birney 2008), is thus inappropriate for microsatellites. An alternative approach, applied in recent studies of human–chimpanzee comparisons (Kayser et al 2006; Vowles and Amos 2006; Kelkar et al 2008), is to identify all microsatellites in each genome and find homologies by comparing positions in a pairwise whole-genome alignment. Although efficient, this task may become impractical when many genomes are compared and probably disproportionate when dealing with highly divergent species that are not expected to share many microsatellite sequences (e.g., human and chicken).…”
Section: Introductionmentioning
confidence: 99%